PERAN GURU DALAM MANAJEMEN BIMBINGAN DAN KONSELING DI PONDOK PESANTREN SALAFIYAH ULA AL FATAH BATAM - Indah Puspita, Fiddiani; Mediana Putri, Aisyah; Nur Azizah, Latifah; Marselina, Marselina; Anggraini, Resi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Guidance and counseling is an important part of the educational process aimed at helping students develop optimally. This study aims to describe the role of teachers in managing guidance and counseling at Pondok Pesantren Salafiyah Ula Al Fatah Batam. This research uses a descriptive qualitative approach with data collection techniques through observation, participation, and documentation during the School Field Introduction (PLP) program.The results show that teachers have an important role in identifying student problems, providing guidance services, and creating a conducive learning environment. In addition, the application of Islamic values contributes to the development of student character, discipline, and independence. Therefore, collaboration between teachers is needed to support the success of guidance and counseling services.